The influence of virtual reality tourism on travel intentions: Enhancing travel decisions with immersive experiences - Ahmed, Tanvir; Rifat, Md. Hasan Imam (Turyzm/Tourism, 2025)
The tourism sector has evolved due to the incorporation of virtual reality (VR) into deeply immersive travel experiences, altering traditional tourism practices and offerings. The study examines how VR tourism affects visitors’ desires, brand truthfulness and travel ease. This study used qualitative methods by engaging fifteen participants in VR travel simulations and participating in semistructured interviews within a controlled environment. Research results indicate that users participating in VR tourism connect deeply with their minds while their dreams of exploration intensify along with reduced traditional travel barriers. The widespread adoption of VR faces significant obstacles due to the diverse preferences of users, high implementation costs, and the limited technological skills of potential travellers. The study demonstrates how virtual reality functions as an expansion pathway for conventional tourism activities, if industry actors can resolve the practical and sensory obstacles linked to its operational deployment.